2021
DOI: 10.1108/ijlm-07-2020-0299
|View full text |Cite
|
Sign up to set email alerts
|

Blockchain in operations for food service distribution: steps before implementation

Abstract: PurposeConsidering the importance of a safe food chain for consumers and the advent of blockchain technology (BT), this research studies a food service (FS) distributor. The research aims to understand the implications related to the functional processes of distribution in FS in which it would be possible to use blockchain to achieve agility, transparency of information and improvements in food safety.Design/methodology/approachFirstly, theory regarding blockchain technology in the supply chain (BT-SC) and FS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 82 publications
(173 reference statements)
0
47
0
1
Order By: Relevance
“…, 2021). See Vivaldini (2021) for an overview of case studies and applications. Within this framework, our contribution investigates the effects that blockchain has on omnichannels and logistics.…”
Section: Introductionmentioning
confidence: 99%
“…, 2021). See Vivaldini (2021) for an overview of case studies and applications. Within this framework, our contribution investigates the effects that blockchain has on omnichannels and logistics.…”
Section: Introductionmentioning
confidence: 99%
“…Our study extends previous conceptual and empirical research in the agrifood industry in that we highlight how substantial investments in hardware, software, and knowledge are needed if companies in the agrifood company want to adopt blockchain [29]. More specifically, we build on previous research and identify those operational barriers that specifically impede the adoption of blockchain technology [30]. Prior studies have also identified lack of government regulation and trust among stakeholders as major adoption barriers [46], which our study confirms and extends by highlighting additional and more refined impediments.…”
Section: Theoretical Contributionsmentioning
confidence: 56%
“…Financial resources are typically considered to be critical for the ability of organizations to acquire blockchain technology [27,28]. The digitalization of agrifood supply chain processes using blockchain technology requires investment in hardware, software, and knowledge [29,30]. Even though this investment may not be as substantial as that required for other supply chain technologies [6], the exact nature of the investment and operating costs are currently not widely and well-understood by managers considering blockchain [31].…”
Section: Financial Constraintsmentioning
confidence: 99%
“…However, we would like to refer the reader interested in the new adaptation of technologies in Vivaldini (2021) and Dora et al (2021), respectively.…”
Section: Discussionmentioning
confidence: 99%